Narrow Role Orientation, Workplace Bullying, and Job Dissatisfaction: Evidence from Pakistan Public Sector HEIs - Habib Ullah; Siraj Ahmed Memon; Muhammad Nadir; Zafar Iqbal (International Journal of Business and Economic Affairs, 2023)
This study aimed to investigate the causes and implications of narrow role orientation among employees. The methodology involved collecting data from 600 employees using a random sampling technique and a 5-point Likert scale questionnaire in English and Urdu. The findings revealed that low income, unequal salaries, critical working conditions, job insecurity, and workplace bullying were significant causes of job dissatisfaction and narrow role orientation. Frequent bullying was found to be more severe and stressful than occasional bullying, leading to an unpleasant work environment and harmful distress among employees. The study’s originality and value lie in shedding light on the impact of workplace bullying on employees’ role orientation, which has implications for organizational effectiveness. The recommendation is for organizations to address the causes of narrow role orientation and take measures to prevent workplace bullying, creating a positive work environment that promotes employee satisfaction and productivity.